Astragalus mongholicus Bunge and Panax notoginseng (Burkill) F.H. Chen Formula for Renal Injury in Diabetic Nephropathy—In Vivo and In Vitro Evidence for Autophagy Regulation - Wen, Dan; Tan, Rui-Zhi; Zhao, Chang-Ying; Li, Jian-Chun; Zhong, Xia; Diao, Hui; Lin, Xiao; Duan, Dayue Darrel; Fan, Jun-Ming; Xie, Xi-Sheng; Wang, Li (Frontiers in Pharmacology, 2020)
Diabetic nephropathy is a serious complications of diabetes mellitus with limited treatment options. It also leads to progressive renal failure, which greatly accelerates the patient’s condition into end-stage renal disease. A&R compound is a Chinese herbal compound widely used to treat chronic kidney diseases in clinic as a traditional medicine in southwest of China. The aim of this study is to explore how A&R work on diabetic nephropathy mouse model and examine whether mTOR/PINK1/Parkin signaling plays a key role in this process. HG-treated renal mesangial cells were employed to evaluated the protective effect of A&R on glomerular cells and the regulation of autophagy. The model group received vehicle, intervention groups received different doses of A&R (1972mg/kg/day, 3944mg/kg/day, 7888mg/kg/day) and irbesartan (19.51972mg/kg/day) for 4 weeks. A&R compound can significantly ameliorate STZ-induced renal injury in mice, specifically can restore serum urea nitrogen (BUN), serum creatinine (Scr), and 24-h urinary albumin. Furthermore, A&R compound can retrieve the reduced autophagy induced by STZ or HG by detecting the expression of mTOR, PINK1, Parkin, Beclin1, p62 and LC3B. Notably, inhibition of autophagy with 3-MA in A&R-treated cells aggravated cellular damage and inactivated PINK1/Parkin signaling, indicating A&R withstanding HG damage through promoting autophagy. In summary, A&R can protect the DN kidneys by upregulating of autophagy and inhibiting inflammation via suppressing mTOR signaling while activating PINK1/Parkin signaling, which provides basic research data for the clinical application of A&R and new drug option for the prevention and treatment of DN.